An Optimized Pathway for Nitrate Removal from Aqueous Solution by Environmentally Friendly Calabash Gourd Shell Adsorbent Based on Experimental Design Methodology - Goran S. Nikolić; Nataša Simonović; Miloš Durmišević; Nada Nikolić; Dragana Marković Nikolić; Milena Nikolić; Grozdanka Bogdanović; Aleksandar Bojić (Separations)
The aim of this research is to optimize the process parameters for nitrate adsorption from aqueous solutions using ammonium modified calabash gourd shell (CGS). Two types of experimental design (DoE) methodology were implemented in the optimization. A full factorial design (FFD) assessed the influence of the main factors on the process response. The efficiency of nitrate adsorption at the predicted optimal conditions by FFD was 78.93%. The study was extended to a central composite design (CCD) within the response surface methodology (RSM) to capture the factors nonlinear effects and optimize the adsorption parameters. The quadratic polynomial model using CCD proved to be useful for understanding the adsorption system’s behavior, locating the optimal process factors, and predicting the adsorption efficiency (R2 > 0.95). The significance of the model terms (A, B, C, D, B2, and C2) is confirmed by F = 74.95 and p < 0.0001. According to the CCD, the optimal adsorption conditions were estimated in the range: initial nitrate concentration 10–20 mg/L, pH 6–7, temperature 20–25 °C, and contact time 25–30 min (desirability 0.996). The predicted and obtained values using FFD and CCD models are very close, which confirms their practical applicability. The repeated test found the nitrate adsorption efficiency (84.9%) using CCD model in the predicted range (80.1–89.6%), which confirms the adequacy and significance of the model. This model could find potential application in real processes for the treatment of nitrate-contaminated water using the environmentally friendly CGS cationic adsorbent.